3D carbon nanocones/metallic MoS2 nanosheet electrodes towards flexible supercapacitors for wearable electronics. (15th July 2021) - Jiang, Zhuosheng; Zhai, Shengli; Huang, Mingzhi; Songsiriritthigul, Prayoon; Aung, Su Htike; Oo, Than Zaw; Luo, Min; Chen, Fuming
Abstract: The ever-increasing demand for powering wearable electronics, energy concern, and climate crisis, arouse attention for developing energy storage systems with high energy and power density, long cycling life, and excellent mechanical flexibility. Herein, we demonstrate a hierarchical 3D electrode for high-performance flexible supercapacitors, in which metallic molybdenum disulﬁde (MoS2 ) nanosheets are uniformly deposited on the surface of carbon nanocones (CNC) grown on carbon cloths (CC), yielding CC-CNC@MoS2 . The 3D CC-CNC substrate provides a large surface for high mass loading of MoS2, a high pathway for fast electron transfers as well as the porous structure for efficient electrolyte ion diffusion to access active materials. Also, the layered structure of metallic MoS2 nanosheets enables large amounts of active sites and facilitates ion transport as well. Benefitting from the rational nanostructure design, the assembled quasi-solid-state supercapacitor yielded a maximum energy density of 0.016 mWh cm −2 and a peak power density of 8.3 mW cm −2, and ultra-high cycling stability over 10, 000 cycles, outperforming many recently reported flexible supercapacitors. Furthermore, the excellent mechanical properties of both CC-CNC substrates and MoS2 nanosheets endow the resulting quasi-solid-state supercapacitors with compelling flexibility for wearable electronics. Finally, an energy storage unit fabricated from the supercapacitors could light an LED, demonstrating its great application potential in wearable electronics. Graphical abstract: Facile synthesis of hierarchical 3D carbon nanocones/metallic MoS2 electrodes for high-performance flexible supercapacitors. Image 1 Highlights: 3D carbon nanocones/M − MoS2 enables fast electron transfer, efficient ion diffusion. Metallic 1T MoS2 has good electrical conductivity & hydrophilicity. Metallic 1T MoS2 provides abundant active sites for large charge storage. Quasi-solid-state supercapacitors delivered excellent performance & flexibility.